Visa Waivers, Multilateral Resistance and International Tourism: Some Evidence from Israel - Daniel Felsenstein; Michael Beenstock; Ziv Rubin (European Regional Science Association (ERSA), 2015)
This paper tests the visa-led tourism hypothesis (VTH) which contends that easing of visa restrictions increases international tourism. Israel acts as a natural laboratory in this case with clear before and after junctures in visa restrictions. We use panel data on tourism to Israel from 60 countries during 1994-2012. In contrast to previous work we take account of non-stationarity in the data and test for the effect of multilateral resistance on tourism. Partial waivers of visa restrictions are estimated to increase tourism by 48 percent and complete waivers increase tourism by 118 percent. Other results include the adverse effect of Israel?s security situation on tourism, the beneficial effect of real devaluation on tourism, and the fact that the elasticity of tourism to Israel with respect to tourism to all destinations is very small.
Keywords: C23; R23; 330; International tourism; visa arrangements; multilateral resistance; panel data